Tubular recovery after acute kidney injury - Fattah, Hadi (Nephron, 2018)
BACKGROUND: A significant portion of patients who suffer from acute kidney injury (AKI) do not fully recover due to largely unclear reasons. Restoration of tubular function has been proposed to be a prerequisite for GFR recovery. SUMMARY: Proximal tubular cells dedifferentiate during the tubular injury phase, which is required for subsequent cell proliferation and replacement of lost epithelial cells. Experimental studies indicate that some cells fail to redifferentiate and continue to produce growth factors (e.g. transforming growth factor β) that can induce fibrosis. Preclinical studies provide first evidence for beneficial effects of inhibiting glucose transport in the proximal tubule in models of ischemia-reperfusion injury (IRI). Comparing renal RNA sequencing data with kidney function during recovery from varying levels of AKI may provide new cues with regard to the sequence of events and help identify key determinants of recovery from AKI. KEY MESSAGES: Tubular recovery after acute kidney injury is vital for recovery of kidney function including improvement of GFR, and likely determines which patients fully recover from AKI or progress to CKD. There is a need to better understand the sequence of events and the processes of tubular cell proliferation and repair, including safe strategies to intervene. The temporary inhibition of selected tubular transport processes, possibly in selected nephron regions, may provide an opportunity to improve tubular cell energetics and facilitate tubular cell recovery with consequences for kidney outcome.